Telipogon sonia-juaniorum (Orchidaceae: Oncidiinae) a new species from Southwestern Ecuador - Zambrano Romero, Bosco Javier; Bogarín, Diego; Solano, Rodolfo (Phytotaxa, 2018)
A new species, Telipogon sonia-juaniorum, from the semi-deciduous montane forests from Southwestern Ecuador is described and illustrated. Information about distribution, habitat, phenology, and conservation status for the new species is provided. The new proposed taxon is morphologically similar to T. standleyi from which it differs by its elliptic-ovate leaves, marginally crenulate, petals obliquely orbicular-ovate, elliptic lip, and column shortly pilose at the base. Telipogon sonia-juaniorum is further compared with T. alexii, T. amoanus, T. boylei, T. lankesteri, T. morganiae, and T. morii.